2019
DOI: 10.1111/jse.12543
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insight into “sky island” species diversification in a mountainous biodiversity hotspot

Abstract: “Sky island” species diversification contributes greatly to mountainous biodiversity. However, the underlying genomic divergence and the inferred drivers remain largely unknown. In this study, we examined the diversification history of five diploid species with three exclusively endemic to the sky islands (mountains) of the Himalaya–Hengduan Mountains biodiversity hotspot. All of them together comprise a clade of the genus Eutrema (Brassicaceae). We resequenced genomes of multiple individuals of the found popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 61 publications
1
35
0
Order By: Relevance
“…The present study presents a potential strategy to overcome these challenges, by first delimiting OTUs from mtDNA data, which allowed us to compare diversity patterns among communities without previous taxonomic information, and using a methodology that can be repeated without introducing potential human error from taxonomic assignment of specimens (Emerson et al, 2011). A caveat of generating OTUs from only mtDNA is that with this data it is not possible to detect interspecific hybridization, which may cause inconsistent phylogenetic relationships between plastome and nuclear-genome trees, and is a potential source of new species in sky-islands (Zhang et al, 2019). However, delimiting OTUs based on molecular data allowed us to perform diversity analyses at the 'species' and haplotype levels.…”
Section: Otus Delimitation Of Tmvb Arthropodsmentioning
confidence: 99%
“…The present study presents a potential strategy to overcome these challenges, by first delimiting OTUs from mtDNA data, which allowed us to compare diversity patterns among communities without previous taxonomic information, and using a methodology that can be repeated without introducing potential human error from taxonomic assignment of specimens (Emerson et al, 2011). A caveat of generating OTUs from only mtDNA is that with this data it is not possible to detect interspecific hybridization, which may cause inconsistent phylogenetic relationships between plastome and nuclear-genome trees, and is a potential source of new species in sky-islands (Zhang et al, 2019). However, delimiting OTUs based on molecular data allowed us to perform diversity analyses at the 'species' and haplotype levels.…”
Section: Otus Delimitation Of Tmvb Arthropodsmentioning
confidence: 99%
“…In contrast, allopolyploidy arises through hybridization between closely related species, and is especially common among flowering plants (Estep et al, 2014). In addition, interspecific hybridization has been suggested as a major source of phylogenetic discordance between nuclear and organellar genomes (Pelser et al, 2010; Wallis et al, 2017; Lee‐Yaw et al, 2019; Wang et al, 2019; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A previous research showed that the individuals of Gentiana siphonantha and G. straminea occurred sympatrically or parapatrically might have experienced historical hybridization and gene flow, which could have resulted in genetic homogenization at ITS (Internal Transcribed Spacer DNA) loci and shared cpDNA haplotypes despite well morphological delimitations (Hu et al, 2016). Except for hybridization after speciation due to the second contact, incomplete lineage sorting could also explain these observed genetic variations between and within each morphological units (Wang et al, 2018;Zhang et al, 2019). If hybridization did occur in the contact zone in the current or past of the two species, such introgressions could be clearly detected by population genomic data.…”
Section: Discussionmentioning
confidence: 99%